The myth of de facto segregation. (February 2019) - Rothstein, Richard
Today, our schools are more racially segregated than at any time in the last 40 years, mainly because the neighborhoods in which they are located are themselves racially segregated. Yet, the U.S. Supreme Court, in its 2007 Parents Involved ruling, prohibited school districts from implementing even modest race-conscious desegregation plans. If people of differing races live in different neighborhoods, the Court found, it is because of de facto segregation (e.g., private individuals' choices about where to live), which the government has no power to remedy. But in fact, argues Richard Rothstein, residential segregation can be traced back to specific decisions made by public officials at the local, state, and federal levels. De facto segregation is a myth, and there's no reason why the government shouldn't take action to integrate schools in segregated neighborhoods .